2014
DOI: 10.3892/ol.2014.2795
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal neuroblastoma: Treatment options and neurological outcome of spinal cord compression

Abstract: Malignant spinal cord compression (MSCC) is a common complication of cancer. Paraspinal neuroblastoma (NB) in the thoracic, abdominal and pelvic regions may extend into the neural foramina causing compression of nerve roots and even the spinal cord. The prompt initiation of specific treatment can improve the neurological outcome. The aim of the present study was to review the clinical features, the management received and the factors that may affect the outcome of patients with MSCC caused by paraspinal NB. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
1
39
0
2
Order By: Relevance
“…However, multivariate analysis indicated a significant association between motor sequela and neurosurgery . The evidence on the role of the symptom–diagnosis interval in the occurrence of late motor deficit is ambiguous; three studies report a significant better outcome with shorter symptom–diagnosis interval, while two studies found no association between the two parameters …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…However, multivariate analysis indicated a significant association between motor sequela and neurosurgery . The evidence on the role of the symptom–diagnosis interval in the occurrence of late motor deficit is ambiguous; three studies report a significant better outcome with shorter symptom–diagnosis interval, while two studies found no association between the two parameters …”
Section: Resultsmentioning
confidence: 96%
“…To determine the outcome of this asymptomatic patient group is not straightforward, since it is often not assessed and/or reported . In three studies, it is explicitly mentioned that the asymptomatic patients do not have any long‐term health problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Late effects may also be related to the primary site of disease. For example, patients with spinal cord compression may have neurologic sequelae including paraplegia or sensory deficits, or alternatively may have significant scoliosis or kyphosis as a result of radiation therapy or laminectomy to treat the cord compression [169]. Learning disabilities are also a potential secondary complication from neuroblastoma treatment, in addition to psychosocial late effects such as low income and lower rates of employment [165].…”
Section: Late Effectsmentioning
confidence: 99%